Integrative Korean Medicine Treatment for Low Back Pain with Butterfly Vertebra: Two Clinical Cases - Dong-Hwan Lee; Oh-Bin Kwon; Jae-Young Lee; Hyo-Rim Kim; Tae-Jun Lee; Sung-Hwan Cho; Kang-Moo Goo; Ja-Yean Son; Seok-Gyu Yang; Yu-Ra Im (MEDrang Inc., 2024)
The butterfly vertebra is a rare congenital anomaly of the spine, which arises from an asymmetric fusion defect in the embryonic vertebral column. This report delineates an integrative Korean medicine treatment administered to two patients who presented with low back pain associated with asymptomatic butterfly vertebrae. The patients received comprehensive treatment comprising acupuncture, Chuna therapy, pharmacopuncture, herbal medicine, and cupping therapy. The efficacy of the treatments was assessed utilizing diverse parameters, including a numerical rating scale, range of motion of the lumbar spine, Oswestry Disability Index, EuroQoL 5-Dimension 5-Level, and patient global impression of change. After the treatment, a notable improvement was noted in the evaluated indicators. These positive outcomes suggest that integrative Korean medicine treatment is suitable for patients experiencing low back pain associated with asymptomatic butterfly vertebrae.